Completely Solvent-free Protocols to Access Phase-Pure, Metastable Metal Halide Perovskites and Functional Photodetectors from the Precursor Salts - Zonghan Hong; Davin Tan; Rohit Abraham John; Yong Kang Eugene Tay; Yan King Terence Ho; Xin Zhao; Tze Chien Sum; Nripan Mathews; Felipe García; Han Sen Soo (iScience, 2019)
Summary: Mechanochemistry is a green, solid-state, re-emerging synthetic technique that can rapidly form complex molecules and materials without exogenous heat or solvent(s). Herein, we report the application of solvent-free mechanochemical ball milling for the synthesis of metal halide perovskites, to overcome problems with solution-based syntheses. We prepared phase-pure, air-sensitive CsSnX3 (X = I, Br, Cl) and its mixed halide perovskites by mechanochemistry for the first time by reactions between cesium and tin(II) halides. Notably, we report the sole examples where metastable, high-temperature phases like cubic CsSnCl3, cubic CsPbI3, and trigonal FAPbI3 were accessible at ambient temperatures and pressures without post-synthetic processing. The perovskites can be prepared up to “kilogram scales.” Lead-free, all-inorganic photodetector devices were fabricated using the mechanosynthesized CsSnBr1.5Cl1.5 under solvent-free conditions and showed 10-fold differences between on-off currents. We highlight an essentially solvent-free, general approach to synthesize metastable compounds and fabricate photodetectors from commercially available precursors. : Devices; Energy Materials; Materials Synthesis Subject Areas: Devices, Energy Materials, Materials Synthesis